2019
DOI: 10.3390/su12010212
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, Migration and Gross Domestic Product from Romania’s Perspective

Abstract: This study analyzes the evolution and trends of the share of remittances in gross domestic product (GDP) and the influence of migration on remittances in Romania. The analysis on data from Eurostat over 2008–2017 has three components: a statistical analysis, an estimation of evolution of indicators, and an estimation of impact of migration on remittances, using polynomial-time regression and difference equation models, respectively. The results showed that GDP and GDP/capita had a permanent increase, meaning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…However, significant communities of Romanian migrant workers are also found in Austria, France, Germany, Greece and the UK. Romanian transnational migrants make a significant contribution to the Romanian economy sending remittances of almost €6 billion home each year, representing almost 2% of GDP (Mehedintu, Soava, and Sterpu 2020).…”
Section: The Return Of Transnational Migrant Workersmentioning
confidence: 99%
“…However, significant communities of Romanian migrant workers are also found in Austria, France, Germany, Greece and the UK. Romanian transnational migrants make a significant contribution to the Romanian economy sending remittances of almost €6 billion home each year, representing almost 2% of GDP (Mehedintu, Soava, and Sterpu 2020).…”
Section: The Return Of Transnational Migrant Workersmentioning
confidence: 99%
“…Remittances are an important source of foreign transfers to developing countries and can be considered a financial mechanism for development. The trend of this currency inflow in the countries of origin obviously illustrates that the value of remittances decreases visibly [8,55], and the strategic analysis of this trend, especially due to the COVID-19 pandemic cannot be optimistic-foreign exchange inflows into countries of origin will fall drastically. The economic and geopolitical situation of the host countries is only one of these factors, but the UK's exit from the EU (1 January 2020) will clearly have a negative impact on remittance inflows to the external balance of payments of emerging countries.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…Thus, international development agencies and governments are considering the potential of employment and remittances to stimulate development in developing countries. In this regard, in a series of previous research on the emerging countries of the European Union [8][9][10], we studied the impact of remittances on economic growth and on poverty; we found that in the short term, the share of remittances in gross domestic product will maintain its upward trend for most of the countries analyzed, but the impact of the COVID-19 pandemic is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When exploring the effect of remittances on economic growth, other authors have used data on both GDP per capita (Abduvaliev & Bustillo, 2019;Comes et al, 2018;Gjini, 2013;Mehedintu et al, 2019 and GDP per capita growth (Cismaș et al, 2019;El Hamma, 2019;Ghosh Dastidar, 2017;Meyer & Shera, 2017).…”
Section: Hypothesis and Model Specificationmentioning
confidence: 99%